Beverage Cans Crusher Machine Patents: A Review (Part V) - Elfasakhany, Ashraf (Asian Review of Mechanical Engineering, 2019)
One of the requirements for any inventor for can crusher machines is to study all previous inventions in the area all over the world. In view of that, the study aims at presenting brief summary of the previous inventions for can crusher machines. We presented here the inventions within years from 1992 to 1993, i.e. couple of years since there are many inventions for such machines around the world; however, other duration periods were already covered in the early papers.